2018
DOI: 10.1186/s12887-018-1099-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementing paediatric early warning scores systems in the Netherlands: future implications

Abstract: BackgroundPaediatric Early Warning Scores (PEWS) are increasingly being used for early identification and management of clinical deterioration in paediatric patients. A PEWS system includes scores, cut-off points and appropriate early intervention. In 2011, The Dutch Ministry of Health advised hospitals to implement a PEWS system in order to improve patient safety in paediatric wards. The objective of this study was to examine the results of implementation of PEWS systems and to gain insight into the attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 24 publications
3
20
0
4
Order By: Relevance
“…More erroneous scores were underscored, rather than overscored. We have no indication that the practice in our organisation differs significantly from other similar centres, and incidental findings from other studies would support this assertion 10 18…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…More erroneous scores were underscored, rather than overscored. We have no indication that the practice in our organisation differs significantly from other similar centres, and incidental findings from other studies would support this assertion 10 18…”
Section: Discussionmentioning
confidence: 59%
“…A recent randomised controlled trial found less than 5% of observation sets had all the required clinical observations for the PEWS 10. A further study found only 69.2% of patient records had a score recorded 1 year after implementation 18. Marked differences in completeness were seen between hospitals with paper-based charts (28.8%) and electronic documentation systems (95.2%).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research shows that the success of implementing clinical guidelines and systems can depend greatly on how much the new practitioner workflow differs from the prior workflow [ 12 , 19 ]. The results from this study comply with these findings, as the implementation rate in the paediatric ward drastically improved after adjusting it to resemble the previous manner of monitoring the patients more closely.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous validated PEWS with varying accuracy in predicting deterioration [ 2 , 9 , 10 , 11 ]. The validation and research on PEWS are mostly done in high‐resource settings [ 2 , 4 , 9 , 10 , 11 , 12 ], while the literature on PEWS in resource‐limited settings is scarce [ 13 ]. Implementing PEWS in high‐resource settings has not shown to result in significant reduction in child mortality, presumably because the baseline mortality is too low to measure the impact of a PEWS, but it results in better child attention [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…В других небольших исследованиях, выполненных в экономически менее благополучных странах, напротив, отмечено положительное влияние внедрения системы раннего предупреждения на эффективность лечения детей в виде снижения частоты неблагоприятных инцидентов в стационарах и снижения частоты летальных исходов от них [12,13], снижения частоты осложнений на догоспитальном этапе оказания медицинской помощи [14]. Отмечено улучшение коммуникации между врачебным персоналом медицинских организаций различного уровня через 1 год после внедрения системы раннего предупреждения за счет единообразной оценки и трактовки полученных результатов [15].…”
Section: показателиunclassified